1980
DOI: 10.1007/bf01478878
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of total cholesterol and protein in urine in patients with the NEPHROTIC syndrome

Abstract: Zusammenfassnng. Bei 42 Patienten mit nephrotischem Syndrom wurde die Protein-und Cholesterinausscheidung im 24 Stundenurin gemessen. Die gefundene positive Korrelation (r--0,76, p<0,01) zwischen Cholesterin und Protein im Urin w/ire vereinbar mit einer gesteigerten glomerul/iren Filtration yon Plasmalipoproteinen als Ursache der Lipidurie beim nephrotischen Syndrom. Sehliisselwarter: Nephrotisches Syndrom -Gesamtcholesterin im Urin Protein im UrinSummary. The excretion of protein and cholesterol in 24 h urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…2). Nagase et al reported that LOX-1 is expressed in the rat glomeruli and tubulointerstitium (10) (19,20). Regrettably, the excretion of lipids or Ox-LDL in urine was not measured in the patients of this study.…”
Section: Detection Of Lox-1 Mrna By In Situ Hybridizationcontrasting
confidence: 54%
“…2). Nagase et al reported that LOX-1 is expressed in the rat glomeruli and tubulointerstitium (10) (19,20). Regrettably, the excretion of lipids or Ox-LDL in urine was not measured in the patients of this study.…”
Section: Detection Of Lox-1 Mrna By In Situ Hybridizationcontrasting
confidence: 54%
“…Increased lipids in urine are also seen in patients with hyperlipidemia and chronic renal disease although not to the extent seen in people with nephrotic syndrome. Accumulation of lipid in the kidney in people has been shown to promote renal disease …”
Section: Introductionmentioning
confidence: 99%
“…Kidney transplantation is the treatment of choice for patients with end-stage renal disease; living donor renal transplantation is superior to cadaveric donor renal transplantation, with higher patient- and graft-survival rates 15 . However, donor renal function is reported to decrease by 30% to 40% after nephrectomy 3 , 16 .…”
Section: Discussionmentioning
confidence: 99%